Prevalence of Maternal Morbidity and Its Association with Socioeconomic Factors: A Population-based Survey of a City in Northeastern Brazil - Tatyana Souza Rosendo; Angelo Giuseppe Roncalli; George Dantas de Azevedo (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Purpose To identify the prevalence of maternal morbidity and its socioeconomic, demographic and health care associated factors in a city in Northeastern Brazil. Methods A cross-sectional and population-based study was conducted, with a design based on multi-stage complex sampling. A validated questionnaire was applied to 848 women aged between 15 and 49 years identified in 8,227 households from 60 census tracts of Natal, the capital of the state of Rio Grande do Norte (RN), Brazil. The main outcome measure was maternal morbidity. The Poisson regression analysis, with 5% significance, was used for the analysis of the associated factors. Results The prevalence of maternal morbidity was of 21.2%. A bivariate analysis showed the following variables associated with an increased number of obstetric complications: non-white race (prevalence ratio [PR] =1.23; 95% confidence interval [95%CI]: 1.04-1.46); lower socioeconomic status (PR = 1.33; 95%CI: 1.12-1.58); prenatal care performed in public services (PR = 1.42; 95%CI: 1.16-1.72): women that were not advised during prenatal care about where they should deliver (PR = 1.24; 95%CI: 1.05-1.46); delivery in public services (PR = 1.63; 95%CI: 1.30-2.03); need to search for more than one hospital for delivery (PR = 1.22; 95%CI: 1.03-1.45); and no companion at all times of delivery care (PR = 1.25, 95%CI: 1.05-1.48). The place where the delivery occurred (public or private) and the socioeconomic status remained significant in the final model. Conclusion Women in a worse socioeconomic situation and whose delivery was performed in public services had a higher prevalence of maternal morbidity. Such an association reinforces the need to strengthen public policies to tackle health inequalities through actions focusing on these determinants.